Inequalities in health: a comparative study between ethnic Norwegians and Pakistanis in Oslo, Norway - Claussen Bjorgulf; Dalen Ingvild; Hussain Akhtar; Dalgard Odd; Syed Hammad; Ahlberg Nora L (BMC, 2006)
Abstract Background The objective of the study was to observe the inequality in health from the perspective of socio-economic factors in relation to ethnic Pakistanis and ethnic Norwegians in Oslo, Norway. Method Data was collected by using an open and structured questionnaire, as a part of the Oslo Health Study 2000-2001. Accordingly 13581 ethnic Norwegians (45% of the eligible) participated as against 339 ethnic Pakistanis (38% of the eligible). Results The ethnic Pakistanis reported a higher prevalence of poor self-rated health 54.7% as opposed to 22.1% (p < 0.001) in ethnic Norwegians, 14% vs. 2.6% (p < 0.001) in diabetes, and 22.0% vs. 9.9% (p < 0.001) in psychological distress. The socio-economic conditions were inversely related to self- rated health, diabetes and distress for the ethnic Norwegians. However, this was surprisingly not the case for the ethnic Pakistanis. Odd ratios did not interfere with the occurrence of diabetes, even after adjusting all the markers of socio-economic status in the multivariate model, while self-reported health and distress showed moderate reduction in the risk estimation. Conclusion There is a large diversity of self-rated health, prevalence of diabetes and distress among the ethnic Pakistanis and Norwegians. Socio-economic status may partly explain the observed inequalities in health. Uncontrolled variables like genetics, lifestyle factors and psychosocial factors related to migration such as social support, community participation, discrimination, and integration may have contributed to the observed phenomenon. This may underline the importance of a multidisciplinary approach in future studies.